IoT security advances in authentication - Liyanage, Madhusanka; Braeken, An 1970-; Kumar, Pardeep 1976-; Ylianttila, Mika (Wiley, 2020)
"The Internet of things (IoT) is the network of physical devices such as vehicles, home appliances sensors, actuators and other electronic devices. The development of internet offers the possibility for these objects to connect and exchange data. Since IoT will pay a major role in our lives, it is important to secure the IoT ecosystem for its value to be realized. Among the various security requirements, authentication to the IoT is importance since it is the first step to prevent the impact of attackers. The book offers an insight into the development of various authentication mechanisms to provide IoT authentication in various levels such as user level, device level and network level. The user-level authentication identifies whether the IoT user is a legitimate user to access the smart object services and what kind of authentication mechanisms can be used. Network level authentication is needed to check the identity of connected IoT devices. This book, therefore, offers reference material which will be important for all relative stakeholders of mobile networks such as network operators, cloud operators, IoT device manufacturers, IoT device users, wireless users, IoT standardization organizations and security solution developers"--
Keywords: Datensicherung; Internet der Dinge; Authentifikation; Computersicherheit; Internet of things / Security measures; Electronic books